PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN PERUSAHAAN - Dewi Yesiana Rahman; Erlin Rohmawati; Ninis Sriyani; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
This research aims to evaluate the influence of organizational culture on the quality of company financial reports. A strong organizational culture, characterized by values ​​such as transparency, accountability and integrity, has a crucial role in supporting good governance practices. The research results reveal that a positive organizational culture significantly contributes to improving the quality of financial reports through effective internal control and compliance with accounting standards. These findings emphasize the importance of organizational culture in producing financial reports that are reliable and trusted by stakeholders.